PENGAWASAN INTERN PROGRAM PEMULIHAN EKONOMI NASIONAL (PEN) PEMERINTAH PUSAT TAHUN 2020: SEBUAH TINJAUAN - Ifham Hakim (Jurnal Acitya Ardana, 2022)
To accelerate the Covid-19 pandemic handling and to recover national economy due to Covid-19 in 2020, Government of Indonesia issued the National Economic Recovery program (PEN). To implement this program, Government of Indonesia allocated IDR 695.2 trillion from Indonesia’s state budget so that the Indonesia’s state budget of 2020’s deficit raises to 5.6%. Internal supervision has a major role in maintaining PEN’s accountability without being a barrier of PEN. This qualitative research, will explain how The Central Governnment doing internal supervision of PEN start from planning, implementing, communicating the results of supervision, and following up on the results of internal supervision. The data used in this research came from articles, laws and regulations, webinars, and direct interviews. This research only focused at the State Audit Board and Development (BPKP) as the coordinator of Internal supervision of PEN without explaining the government internal supervisory apparatus’s (APIP) point of view. The result of this study showing the correspondency between PEN’s internal supervision and applicable law and regulations which brings the objectives of this program to be achieved.